2007
DOI: 10.1111/j.1469-8137.2007.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for post‐translational regulation of NrtA, the Aspergillus nidulans high‐affinity nitrate transporter

Abstract: Summary• Here, influx and efflux of , and net fluxes of and , were measured in Aspergillus nidulans mutants niaD171 and niiA5 , devoid of nitrate reductase (NR) and nitrite reductase (NiR) activities, respectively.• Transcript and protein abundances of NrtA, the A. nidulans principal high-affinity transporter, were determined using semiquantitative reverse transcriptionpolymerase chain reaction and western blots, respectively.• influx in niaD171 was negligible relative to wild-type values, whereas efflux to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…One possibility is that its primary responsibility is for NO 2 À efflux under conditions where NO 3 À uptake and reduction exceed the organism's capacity for further assimilation. It is well documented that when NO 3 À uptake and reduction exceed capacity for reduction to NH 4 + , NO 2 À is excreted (Collos, 1998;Jia and Cole, 2005;Wang et al, 2007). Disruption of the nitA gene, in the double mutant background in the present study, reduced NO 2 À uptake to very low rates that were pHdependent in a manner suggestive of passive permeation in the form of HNO 2 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…One possibility is that its primary responsibility is for NO 2 À efflux under conditions where NO 3 À uptake and reduction exceed the organism's capacity for further assimilation. It is well documented that when NO 3 À uptake and reduction exceed capacity for reduction to NH 4 + , NO 2 À is excreted (Collos, 1998;Jia and Cole, 2005;Wang et al, 2007). Disruption of the nitA gene, in the double mutant background in the present study, reduced NO 2 À uptake to very low rates that were pHdependent in a manner suggestive of passive permeation in the form of HNO 2 .…”
Section: Discussionmentioning
confidence: 59%
“…In order to measure nitrite efflux samples of 13 NO 3 were reduced to 13 NO 2 À by use of a cadmium column following the method of McElfresh et al (1979). The double mutant, strain nrtA747 nrtB110, was incubated in standard influx medium containing 500 lM 13 NO 2 À for 30 min and then the labelled medium was replaced by identical non-labelled medium as described in Wang et al (2007) for the determination of 13 N efflux. Non-labelled media were replaced at intervals of 1 min (five times) and 2 min (eight times) for a total of 21 min and the eluates counted to detect tracer leaving the mycelia.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…However, when nitrate is scarce, its fine regulation by Npr1-mediated phosphorylation targets it to the plasma membrane, facilitating nitrate uptake and consequently nitrate assimilation gene induction (12). There is also strong evidence on the post-translational regulation of A. thaliana NRT2.1 and Aspergillus nidulans NrtA (13,14).…”
mentioning
confidence: 99%
“…Interestingly, nitrogen limitation renders the lowest levels of Ynt1 ubiquitinylation, and consequently it accumulates at the plasma membrane. More recently, it has been suggested that nitrate transporters NrtA and NRT2.1 from Aspergillus nidulans and Arabidopsis thaliana undergo post-translational regulation but the molecular mechanisms are so far unknown (7,14,15).…”
mentioning
confidence: 99%